The Impact of Credit Risk on the Sensitivity of Investment Portfolios: Evidence from Iraqi Banks - Marzouq, M.M. Salam Eidhan; Imran, M.M .Mortada Hassan (American Journal of Economics and Business Management, 2025)
Credit risk is one of the most prominent concerns of commercial banks, as it reflects the greater obsession to re-operate the funds of others within the commercial bank in safe ways while ensuring the greatest possible profits. From this standpoint, the research idea began by explaining the concept of credit risk and its most prominent types in detail, as well as explaining the importance of investment portfolios and their role in developing bank funds. The research also demonstrated the nature of the correlation and impact between credit risk and the sensitivity of investment portfolios to it. The research was limited to credit risk indicators (total loans to total current assets and the provision for expected credit losses to total loans) as an independent variable, considering that these indicators are the most influential in determining the extent of credit risk in commercial banks. The dependent variable is the sensitivity of investment portfolios, whose indicators were used (the percentage of each investment portfolio to the total investments during the research years). Two banks (Al-Mansour Investment Bank and Mosul Bank for Development and Investment) were chosen as a purposive sample for the research, and a time series spanning four years (2019-2022). The researcher proceeds from the hypothesis that there is a strong and significant correlation and impact between the independent and dependent variables, and attempts to prove this using financial and statistical analysis.